Scientifics basis for refusing complete repair of the heart in all cases of tetralogy of Fallot. Indications of the Potts and Clalock operation - Castellanos, A.; Giral Casielles, A. (Revista Cubana de Pediatría, 2022)
Presentado en el Primer Symposium Internacional sobre Enfermedades Cardiovasculares de la Fundación "Shiao", Julio 27-30, 1959. Versión en inglés.